Development and characterization of a protein based mineralizing bio-ink - Mitzakoff, Anna Marie-Thérèse (2024)
Despite the outstanding mechanical properties of human bone, bone fractures to this day impose a challenge on bone repair therapy. In regenerative medicine, tissue engineering has gained increasing interest for the synthesis of biologically derived tissues. For bone synthesis, tissue engineering uses so-called scaffolds which mimic the structural bone environment. 3D-printing is a popular option for the fabrication of these complex scaffolds. Whilst some methods rely on the interplay between biological components and structurally distinct scaffolds, which can trigger osteogenesis, other methods explore the development of novel materials that can be processed to mimic the structural and mechanical properties of human bone. However, challenges such as biocompatibility, mechanical strength, and resolution, remain. Therefore, the development of biocompatible materials, which can exhibit desired biological and mechanical properties once processed into scaffolds, is crucial to satisfy the unmet needs in bone regeneration therapy research. Previous studies show improvements with respect to biocompatibility and osteoinductivity of bone tissue engineering scaffolds through the synthesis of biomineralized scaffolds. A popular choice in the selection of biomaterials suitable for these scaffolds is Hydroxyapatite. However, three-dimensional scaffolds produced from pure Hydroxyapatite are highly brittle, making them unsuitable for load barding applications. Through the development of composite materials, which integrate a polymeric phase into these inorganic constructs, the materials’ durability can be enhanced. Even though this approach has improved the mechanical performance of mineralized scaffolds, issues such as interfacial bonding between the phases remain. Hence, the clinical need for the establishment of suitable biomaterials for bone tissue engineering remains. Polypeptides have been found to be play a crucial role in biomineralization. In previous work, polypeptide-based membranes have been synthesized. The used polypeptide sequence can undergo stimuli triggered self-assembly that can template the growth of hierarchically mineralized structures that can exhibit the same mechanical properties as bone. In this thesis, this proposed platform was extended to enable the controlled extrusion of shapely filaments that could undergo hierarchically structured biomineralization. The work ranged from formulation development and optimization to material characterization and process integration into an automated extrusion system. Two novel formulations were processed into membrane- and gel configurations. Control strategies were developed to understand parameters that contribute to self-assembly of the integrated polypeptide sequence. Furthermore, a mechanism that triggers biomineralization in the presented formulations was proposed. Two-dimensional grid structures were successfully printed. However, the rheological properties of the established bio inks were not fully understood, and further work is required to optimize the choice of print substrate.